Heteroatom-Tethered ω-Alkenylallylboronates: Stereoselective Synthesis of Heterocyclic Derived Alcohols - Garnes-Portolés, Francisco; Miguélez, Rubén; Grayson, Matthew N.; Barrio, Pablo (Synthesis, 2022)
The synthesis of ω-alkenylallylboronates using a heteroatom tether to join both functional groups is described for the first time. Then, these unprecedented compounds were used in a tandem Brønsted acid catalyzed allylboration/ring-closing metathesis (RCM) reaction affording heterocyclic derived alcohols as single diastereoisomers. The low enantioselectivity observed in the asymmetric version using a chiral phosphoric acid catalyst was studied theoretically.
Keywords: allylboration; ring-closing metathesis; tandem catalysis; heterocycles; alcohols; stereoselective synthesis